Energy Consumption and Economic Growth In Turkey: An Empirical Analysis - Nurgün Topallı; Mehmet Alagöz (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2014)
Energy is one of the most important fundamental inputs of the economy and social life. Globally; increasing population, economic growth, urbanization, and technological developments have been increasing energy needs of countries. However, the fact that the fossil fuels such as oil, coal and natural gas is limited and rising energy prices led countries to find alternative sources of energy. The country’s energy dependency is increasing day to day. Relationship between energy and economic growth for developed and developing countries is a hotly debated topic. Especially for developing countries requires more energy to achieve economic growth. In term of Turkey which is particularly dependent on foreign energy is important to determine the direction of the relationship. The ampiric literature related with causality between energy consumption and economic growth show different results according to periods and methods used. In some studies a uni-directional causality is found running from energy consumption to economic growth and in some studies a uni-directional causality is found running from economic growth to energy consumption. While some results indicate no causality between variables, the others indicate bi-directional causality. The aim of this study is to examine relationship between electricity consumption and economic growth in Turkey during the period 1970-2009. Real GDP per capita and electricity per capita variables are used. Firstly, NG Perron and Phillips Perron unit root tests are used to verify the order of integration of the variables. Johansen cointegration test and vector error correction model are employed to examine the relationship. All variables are found stationary in the first difference. According to Johansen cointegration test it is concluded that there is long run cointegration between variables. The results indicate that there is a cointegration vector between the real GDP and the electricity consumption in the long- run. Both short and long-run unidirectional causality from real GDP to electricity consumption is observed. Besides, according to Toda Yamamoto Granger Causality test there is found uni-directional causality from real GDP to electricity consumption. This results can be interpreted as advancement of the countries’ economy, there has been increase in energy consumption, particulary in electricity consumption. Due to high income, consumers consume more and more electricity. According to the findings obtained from this study, energy conservation policies may be applied in order to reduce energy consumption in Turkey. The uni-directional causality running from economic growth to energy consumption implies that energy conservation policies may not unfavourable effects on economic growth.